Increasing The Selling value of Citronella Oil Through Processing Citronella Oil for Citronella Farmers di Pesisir Selatan: Peningkatan Nilai Jual Minyak Serai Wangi Melalui Pengolahan Minyak Serai Wangi Untuk Petani Serai Wangi Di Pesisir Selatan - suciandri suciandri; Jusmardi Jusmardi; Erik Fernandes Erik; Junil Adri Junil (Institut Riset dan Publikasi Indonesia, 2023)
Problems faced by the Serai Wangi Harum Mandeh farmer group. Based on field observations, information was obtained from Jafrizal as chairman of the Serai Wangi Harum Mandeh farmer group. The problems of citronella farmers start in terms of land, planting and harvesting before processing citronella into oil. The most important problem to be overcome is that equipment is needed to process citronella into oil in order to increase the selling value. The processing system is carried out using traditional and conventional methods. This will result in less than optimal results from citronella oil production. The solution offered to overcome this problem, the community service team innovated to increase the production of citronella oil by the Harum Mandeh Serai Farmers Group in Kenagarian Mandeh, Koto XI Tarusan District, Pesisir Selatan Regency. The planned citronella distillation equipment has an evaporation (stem) concept with a tubular design and this can help farmers increase the yield of citronella oil processing. The service team will provide knowledge to the Mandeh fragrant citronella farmer group about how the distillation system complies with Standard Operating Procedures (SOP), maintenance systems and occupational safety in processing citronella oil. The result of this service is in the form of citronella oil refining processing equipment that is ready to be operated by farmers in accordance with the procedures presented.